KAIB 2020: "Konferensi Antarabangsa Islam Borneo" soars to greater heights - Chung, Ellen (Universiti Teknologi MARA, Sarawak, 2021)
Dubbed as KAIB Online 2020, with the theme “World Halal Industry: Opportunities and Challenges Post COVID-19 Pandemic”, UiTM Sarawak has successfully organised Konferensi Antarabangsa Islam Borneo (KAIB) 2020 amidst the COVID-19 pandemic. Eight speakers from different parts of the world, namely Australia, Brunei, China, Indonesia, Malaysia, Spain and Taiwan, presented their views with regard to the Conference theme. KAIB Online 2020 was jointly organised by UiTM Sarawak together with Universiti Teknologi Mara Sabah, Institute Halal of Spain, Universiti Islam Sultan Sharif Ali Brunei Darussalam, Kolej Universiti Perguruan Ugama Seri Bagawan Brunei Darussalam, Universitas Lambung Mangkurat Banjarmasin Indonesia, Universitas Mulawarman Samarinda Indonesia, Institut Agama Islam Negeri Pontianak Indonesia, Universitas Islam Negeri Antasari Samarinda Indonesia and Institut Agama Islam Negeri Palangka Raya Indonesia.